Treatment of distal radioulnar joint dislocation with spontaneous rupture of extensor tendon by Sauve–Kapandji osteotomy assisted by wrist arthroscopy: A case series and literature review. Issue 22 (June 2018) - Qian, Hui; Chen, Guozhao; Liu, Zongbao
Abstract: Rationale: Dislocation of the distal radioulnar joint and injury to distal forearm are commonly encountered. However, delayed diagnosis or misdiagnosis has been relatively rare due to improved diagnosis and treatment. Treatment of old dislocation of radioulnar joint is challenging due to development of secondary chronic instability and difficulties in restoration of joint function. Patient concerns: This report describes three cases of patients complained about inability to extend their little fingers. Diagnoses: Local examination and X-ray revealed chronic ulnar joint dislocation. Intervention: Wrist arthroplasty was used to perform ulnar distal articular cleansing and repair of the triangular fibrocartilage complex (TFCC) articular cartilage. The Sauve-Kapandji osteotomy was performed to treat radial joint dislocation and stabilize ulnar joint. Repair of spontaneous fracture of the extensor tendon was also performed. Postoperative gypsum was used for immobilization for 4 weeks. Outcomes: The follow-up results are reported. Based on Cooney wrist score, the preoperative scores were poor (55, 50, 60), while the post-operative scores were excellent (90, 85, 90) in all 3 cases. Lessons: Early and accurate diagnosis and treatment is important for the recovery of distal radius fracture for patients with dislocation of the ulnar joint. The correct treatment determines the degree of later functional recovery. Early surgical treatment is recommended for patients with unsatisfactory reset. Delayed diagnosis and treatment often lead to chronic and persistent lower ulnar joint subluxation or dislocation, or even osteoarthritis. All patients in this report showed great improvement in wrist function after surgery.